Functional analysis of embolism induced by air injection in Acer rubrum and Salix nigra - Melcher, Peter J.; Zwieniecki, Maciej A. (Frontiers in Plant Science, 2013)
The goal of this study was to assess the effect of induced embolism with air injection treatments on the function of xylem in Acer rubrum L. and Salix nigra Marsh. Measurements made on mature trees of A. rubrum showed that pneumatic pressurization treatments that created a pressure gradient of 5.5 MPa across pit membranes (DPpit) had no effect on stomatal conductance or on branch-level sap flow. The same air injection treatments made on three year old potted A. rubrum plants also had no effect on whole plant transpiration. A separate study made on mature A. rubrum trees showed that 3.0 and 5.5 MPa of DPpit values resulted in an immediate 100% loss in hydraulic conductance (PLC) in petioles. However, the observed change in PLC was short lived and significant hydraulic recovery occurred within 5-10 minutes post air pressurization treatments. Similar experiments conducted on S. nigra plants exposed to DPpit of 3 MPa resulted in a rapid decline in whole plant transpiration followed by leaf wilting and eventual plant death, showing that this species lacks the ability to recover from induced embolism. A survey that measured the effect of air-pressurization treatments on seven other species showed that some species are very sensitive to induction of embolism resulting in leaf wilting and branch death while others show minimal to no effect despite that in each case, the applied DPpit of 5.5 MPa significantly exceeded any native stress that these plants would experience naturally.